Visfatin derived from ascites promotes ovarian cancer cell migration through Rho/ROCK signaling-mediated actin polymerization. Issue 3 (May 2015) - Li, Yan; Li, Xun; Liu, Kui-Ran; Zhang, Jia-Ning; Liu, Yang; Zhu, Yu
Abstract : Ovarian cancer is characterized by a rapid intraperitoneal spread combination with ascites accumulation. However, the exact mechanisms for ovarian cancer intraperitoneal dissemination remain unknown. Visfatin has recently been established as a novel adipokine and its serum level is increased in various cancers. Here, we identified that the elevated level of visfatin in ascites was associated with ovarian cancer intraperitoneal dissemination. Using the transwell cell migration assay and the wound-healing assay, we found that ascites-derived visfatin could promote migration of Caov-3 cells. Meanwhile, visfatin could induce the aggregation of actin stress fibers and the formation of lamellipodia and filopodia in Caov-3 cells, concomitant with a shift of G-actin to F-actin. Inhibition of actin polymerization with cytochalasin D obviously abolished the effects of visfatin on the migration of Caov-3 cells. Further results showed that visfatin triggered Rho activation and its downstream cofilin phosphorylation in a time-dependent manner, which led to actin polymerization. More importantly, visfatin-induced Caov-3 cell migration was effectively blocked by C3 exoenzyme and Y27632, Rho, and ROCK inhibitor, respectively. Thus, our study showed that ascites-derived visfatin promoted migration of ovarian cancer cells through Rho/ROCK signaling-mediated actin polymerization, which was required for ovarian cancer intraperitoneal dissemination. These findings offered a novel molecular mechanism responsible for ovarian cancer intraperitoneal dissemination, which might be a potential target for ovarian cancer management.